Use and outcomes of the PK Papyrus covered stent in France: SOS PK Papyrus Registry. Issue 5 (21st October 2020) - Hernández‐Enríquez, Marco; Belle, Loic; Madiot, Hende; Pansieri, Michel; Souteyrand, Geraud; de Poli, Fabiel; Piot, Christophe; Boueri, Ziad; Gerbaud, Edouard; Boiffard, Emmanuel; Benamer, Hakim; Lattuca, Benoit; et al.
Abstract: Objectives: To evaluate the rate of procedural success and long‐term outcomes of the PK Papyrus (PKP) covered stent (CS). Background: CS are essential in the treatment of coronary artery perforation (CAP). They have also been used to treat coronary artery aneurysms. Limited evidence is available on clinical outcomes with the PKP. Methods: This was a multicenter, observational, retrospective, and prospective study. Consecutive patients undergoing intentional PKP implantation in 22 centers in France were included. The primary endpoint was the rate of procedural success. Secondary endpoints included rates of death, myocardial infarction (MI), target lesion revascularization (TLR), in‐stent restenosis (ISR), and stent thrombosis (ST). Results: Data from 130 patients were analyzed (mean age 72.5 ± 10.5 years; 71% men). The main indication for PKP was CAP, in 84 patients (65%). Delivery success was achieved in 95% and procedural success in 91%. During the in‐hospital stay, 15 patients died (12%) and 7 (5%) presented with ST. Data from 127 patients were available at 19.2 ± 12.8 month follow‐up. Thirty‐three patients died (26%), 15 (12%) had an MI and 21 (17%) presented with TLR. TLR was due to ISR in 12 patients (9%), 10 had definite ST (8%) and 1 patient for stent under‐expansion. Conclusions: The principal indication for PKP was CAP. PKP had high rates of delivery and procedural success. At long‐term follow‐up, there was a high rate of TLR, mainly due to ISR and ST. These results are consistent with previously reported data in these clinical settings.